Defluoridation of Fluoride-Contaminated Wastewater Using ZnCl₂-Modified biochar: Kinetics and Isotherm Analysis - Hirpha Adugna Areti; Mani Jayakumar; Lata Deso Abo; B. S. Naveen Prasad; Suresh Krishnan; Nufbek Worku Salodi; Kenenesa Alemu Jima; Amansisa Aduna Waktola (Water, Air, & Soil Pollution, 2026)

Monsoon-driven seasonal variability in sediment texture of embayed beaches along the central west coast of India - Puneet Kumar Mishra; Mani Murali R; Deepika Dwivedi; SK Ariful Hossain; Santhosh Kumar S; Jayakumar Seelam; Shincy Francis; Richa Rai (Regional Studies in Marine Science, 2026)

Deciphering Environmental Drivers on Plankton Dynamics in Punnakayal–Pazhayakayal Estuarine Complex, Southern Coast of India - Kamei Ringjonmeilu; N. Jayakumar; R. Durairaja; V. Rani; T. Ravikumar; R. Saravanan; C. Sudhan; Adyasha Sahu; J. Joyson Paul; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Reproductive Traits and Population Characteristics of Atule mate (Cuvier, 1833) From the Gulf of Mannar: Implications for Minimum Legal Size - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; K. Karuppasamy; Percy Paulin J; S. Pearlin Arul Granap; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

A new remote sensing-derived high resolution eco-physiological land use land cover (HR Eco-P LULC) product in support of regional climate modeling over the Indian landscape - Kshama Gupta; Bhoomika Ghale; Shailja Mamgain; Arijit Roy; Shweta Bhati; T.J. Anurose; A. Jayakumar; Abhishek Danodia; Harish Chandra Karnatak; Pramod Kumar; Raghavendra Pratap Singh; Murali Krishna Gumma; et al. (Remote Sensing Applications: Society and Environment, 2026)

Reproductive biology and population dynamics of the five-lined snapper Lutjanus quinquelineatus (Bloch, 1790) from the Gulf of Mannar: implications for establishing minimum legal-size limits - M. Sharumathi; N. Jayakumar; R. Durairaja; J. Joyson Paul; R. G. Sasikumar; K. Karuppasamy; S. Parkavi; S. Pearlin Arul Granap (Environmental Biology of Fishes, 2026)

Demographic Characteristics and Exploitation Status of the Blue Swimming Crab Portunus pelagicus (Linnaeus, 1758) Along the Palk Bay Coast, Southeast India - Pearlin Arul Granap S.; Durairaja R.; Jayakumar N.; Ranjith L.; Sudhan C.; Karuppasamy K.; Kalaiarasan M.; J. Joyson Paul; Nandhakumar M. (Thalassas: An International Journal of Marine Sciences, 2025)

Artificial intelligence in disaster management: achievements, challenges, and prospects - Junxiang Xu; Divya Jayakumar Nair; S. Travis Waller (Natural Hazards, 2025)

Tailoring CdSe nanoparticles at different pH levels for improved methylene blue photodegradation - X. Venci; Amal George; Mohammed Alsawat; S. Rahul; Subhav Singh; Sivarasan Ganesan; C. Dominic Savio; A. Dhayal Raj; S. John Sundaram; G. Jayakumar (Environmental Geochemistry and Health, 2025)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

The role of macroalgae in modulating coral calcification: Mixed species responses in a changing reef environment - B. Manikandan; P. Sawant; P.K. Maurya; Ashish Pal; T.A. Naik; J. Ravindran; Sayeri Paul; T. Lad; S. Prabhudesai; K. Jayakumar (Marine Environmental Research, 2025)

Substrate Effect on the Contribution of Ammonium and Urea to Marine Nitrification and Nitrous Oxide Production - Weiyi Tang; Catherine Hexter; Rongbo Dai; Samantha G. Fortin; John C. Tracey; Naomi Intrator; Moriah A. Kunes; Xianhui S. Wan; Amal Jayakumar; Dalin Shi; Bess B. Ward (Environmental Microbiology, 2025)
Nitrification (microbial oxidation of ammonia to nitrite and nitrate) controls nitrogen speciation and is the main source of nitrous oxide (N 2 O) in the ocean. It was recently shown that the most abundant marine ammonia oxidizers, the ammonia‐oxidising archaea (AOA), are also capable of oxidising urea, providing a previously ignored source of nitrite. Here, we show that the relative magnitude of urea and ammonia oxidation rates, and the relative rates of N 2 O production from the two substrates, is correlated with the ratio of the substrate concentrations. By examining all reported measurements of urea and ammonium concentrations and the paired urea and ammonia oxidation rates, we show that this relationship likely holds across the global ocean. Examination of newly acquired and previously published metagenomic data shows that the fraction of AOA with the genetic capability for urea oxidation increases with the urea:ammonium ratio, rather than depending on the urea or ammonium concentration alone. These results corroborate the correlation between substrate ratios and oxidation rate ratios, and extend it to N 2 O production. This may help explain the distribution of nitrification rates and N 2 O production in the ocean.

Stratified enhanced interval-valued q-rung orthopair picture bipolar fuzzy decision-making approach for municipal solid waste disposal technique selection - T. N. Parthasarathy; C. S. Thilagasree; T. Jayakumar; V. Simic; D. Pamucar (International Journal of Environmental Science and Technology, 2025)

Whole Genome Sequencing of Carbapenem-Resistant Enterobacter hormaechei Isolated from Thiruvananthapuram, Kerala (India) - Parvathi Vaikkathillam; Praveen Kumar; S. Manjusree; Minsa Mini; Devi Jayakumar; Amjesh Revikumar (Indian Journal of Microbiology, 2025)

Length-Weight Relationships and Condition Factor of 15 Coastal Fish Species (Family: Lethrinidae) of the Gulf of Mannar, Southeast Coast of India - Sanjay Chandravanshi; N. Jayakumar; R. Durairaja; S. Aanand; E. Suresh; C. Sudhan; M. Kishore Kumar; Mahesh Chand Sonwal; Adyasha Sahu (Thalassas: An International Journal of Marine Sciences, 2025)

Gingival Mesenchymal Stem Cells: A Periodontal Regenerative Substitute - Sonia S. Shetty; S. Sowmya; Aathira Pradeep; R. Jayakumar (Tissue Engineering and Regenerative Medicine, 2025)

Biomimetic nanocomposite cryogel with enhanced peptide binding promotes therapeutic angiogenesis and bone regeneration - Sivashanmugam Amirthalingam; Seoyeon Kim; Dayeon Roo; Kyung Min Ryu; Jiwoon Jeong; Perrine M'Pemba Hennebert; Kyoung-Ha So; Jayakumar Rangasamy; Nathaniel S. Hwang (Chemical Engineering Journal, 2024)

Assessment of extreme rainfall events for iFLOWS Mumbai in NCUM regional forecasting system - Mohan S. T; Raghavendra Ashrit; Kondapalli Niranjan Kumar; Upal Saha; D. Nagarjuna Rao; A. Jayakumar; Saji Mohandas; V. S. Prasad (Natural Hazards, 2024)

Oral In-Situ Nanoplatform with Balanced Hydrophobic-Hydrophilic Property for Transport Across Gastrointestinal Mucosa - Esha S. Attar; S. Jayakumar; Padma V. Devarajan (AAPS PharmSciTech, 2024)

Dynamics of marine debris in the point calimere wildlife and bird sanctuary wetland, southeastern coast of India - Selvam Kesavan; N. Jayakumar; S. Santhoshkumar; A. Subburaj; S. Balasundari (Ocean & Coastal Management, 2024)

Biomass patterns in Srivilliputhur Wildlife Sanctuary: exploring factors and gradients with machine learning approach - Neha Jaiswal; S. Jayakumar (Environmental Monitoring and Assessment, 2024)

Phenotypic and genetic characterization of unexplored, potential cattle population of Madhya Pradesh - Jayakumar Sivalingam; S. K. Niranjan; Dinesh Kumar Yadav; S. P. Singh; Nidhi Sukhija; K. K. Kanaka; P. K. Singh; Ajit Pratap Singh (Tropical Animal Health and Production, 2024)

Antibiofilm potential of gallic acid against Klebsiella pneumoniae and Enterobacter hormaechei : in-vitro and in-silico analysis - Pooja P. Rajan; Praveen Kumar; Minsa Mini; Devi Jayakumar; Parvathi Vaikkathillam; Sneha Asha; Aparna Mohan; Manjusree S (Biofouling, 2023)

Analysis of Temporal Patterns of Ichthyofaunal Bycatch Landed Along the Thoothukudi Coast, Gulf of Mannar, India - S. Santhoshkumar; P. Jawahar; A. Srinivasan; N. Jayakumar; A. Subburaj; K. Karuppasamy; M. Srihari (Thalassas: An International Journal of Marine Sciences, 2023)

Equity analysis and improvement in transportation resilience optimisation at the pre-event stage - Tingting Zhang; Chence Niu; Divya Jayakumar Nair; Vinayak Dixit; S. Travis Waller (Transportation Research Part D: Transport and Environment, 2023)

Comparative assessment of growth performance of indigenous and cross-bred calves subjected to combined stressors (heat and nutritional) - C. G. Shashank; R. G. Prashant; Parveen Kumar; Nitish A. Kulkarni; Manish Tiwari; S. Jayakumar; V. Sejian (International Journal of Biometeorology, 2023)

Etiology behind canine uterine inertia: Role of uterine expression of MLCK4, MYH2, and PKC genes - Magnus P.K.; Jayakumar C.; Naicy T.; Lali F.A.; Hiron M. Harshan; Abhilash R.S.; Ajithkumar S. (Animal Reproduction Science, 2023)

Development of bio-based adhesive using tannery shaving dust: Process optimization using statistical and artificial intelligence techniques - Ejigayehu Chakiso Gebremariam; Yohanes Chekol Malede; S. Venkatesa Prabhu; Venkatramanan Varadharajan; S. Manivannan; Mani Jayakumar; Baskar Gurunathan (Bioresource Technology Reports, 2023)

Multi-faceted CRISPR-Cas9 strategy to reduce plant based food loss and waste for sustainable bio-economy – A review - Palanivel Hemalatha; Ebrahim M. Abda; Shipra Shah; S. Venkatesa Prabhu; M. Jayakumar; N. Karmegam; Woong Kim; M. Govarthanan (Journal of Environmental Management, 2023)

Current and prognostic overview on the strategic exploitation of anaerobic digestion and digestate: A review - S. Chozhavendhan; G. Karthigadevi; B. Bharathiraja; R. Praveen Kumar; Lata Deso Abo; S. Venkatesa Prabhu; Ramalingam Balachandar; Mani Jayakumar (Environmental Research, 2023)

Long-Term Sequelae of COVID-19 in Experimental Mice - Michael J. Paidas; Daniela S. Cosio; Saad Ali; Norma Sue Kenyon; Arumugam R. Jayakumar (Molecular Neurobiology, 2022)
We recently reported acute COVID-19 symptoms, clinical status, weight loss, multi-organ pathological changes, and animal death in a murine hepatitis virus-1 (MHV-1) coronavirus mouse model of COVID-19, which were similar to that observed in humans with COVID-19. We further examined long-term (12 months post-infection) sequelae of COVID-19 in these mice. Congested blood vessels, perivascular cavitation, pericellular halos, vacuolation of neuropils, pyknotic nuclei, acute eosinophilic necrosis, necrotic neurons with fragmented nuclei, and vacuolation were observed in the brain cortex 12 months post-MHV-1 infection. These changes were associated with increased reactive astrocytes and microglia, hyperphosphorylated TDP-43 and tau, and a decrease in synaptic protein synaptophysin-1, suggesting the possible long-term impact of SARS-CoV-2 infection on defective neuronal integrity. The lungs showed severe inflammation, bronchiolar airway wall thickening due to fibrotic remodeling, bronchioles with increased numbers of goblet cells in the epithelial lining, and bronchiole walls with increased numbers of inflammatory cells. Hearts showed severe interstitial edema, vascular congestion and dilation, nucleated red blood cells (RBCs), RBCs infiltrating between degenerative myocardial fibers, inflammatory cells and apoptotic bodies and acute myocyte necrosis, hypertrophy, and fibrosis. Long-term changes in the liver and kidney were less severe than those observed in the acute phase. Noteworthy, the treatment of infected mice with a small molecule synthetic peptide which prevents the binding of spike protein to its respective receptors significantly attenuated disease progression, as well as the pathological changes observed post-long-term infection. Collectively, these findings suggest that COVID-19 may result in long-term, irreversible changes predominantly in the brain, lung, and heart.

Proposing a Hybrid Genetic Algorithm based Parsimonious Random Forest Regression (H-GAPRFR) technique for solar irradiance forecasting with feature selection and parameter optimization - Josalin Jemima J.; Nelson Jayakumar D.; Charles Raja S.; Venkatesh P. (Earth Science Informatics, 2022)

Mechanism underpinning the sharpening of orientation and spatial frequency selectivities in the tree shrew (Tupaia belangeri) primary visual cortex - Yamni S. Mohan; Sivaram Viswanathan; Jaikishan Jayakumar; Errol K. J. Lloyd; Trichur R. Vidyasagar (Brain Structure and Function, 2022)

Meso-scale foreshore evolution in low-energy, storm-dominated tropical west coast of India: Implications for shoreline management - Venkatraman S Hegde; Shailesh R Nayak; Girish K Huchchannavar; P A Krishnaprasad; A S Rajawat; G Shalini; S Jayakumar; Kanchanagouri D Gosavi; Lavanya G Hegde (Journal of Earth System Science, 2022)

A new species of Congrid eel, Ariosoma melanospilos sp. nov., from Indian waters with taxonomic description of A. dolichopterum (Congridae: Bathymyrinae) - Paramasivam Kodeeswaran; T. K Teena Jayakumar; S. Akash; T. T. Ajith Kumar; Kuldeep Kumar Lal (Marine Biodiversity, 2021)

Assessment of the Efficacy of Lightning Forecast Over India: A Diagnostic Study - A. Sandeep; A. Jayakumar; M. Sateesh; Saji Mohandas; V. S. Prasad; E. N. Rajagopal (Pure and Applied Geophysics, 2021)

Rice GWAS reveals key genomic regions essential for salinity tolerance at reproductive stage - Arvinder Singh Warraich; S. L. Krishnamurthy; Balwinder Singh Sooch; N. M. Vinaykumar; B. M. Dushyanthkumar; Jayakumar Bose; Parbodh Chander Sharma (Acta Physiologiae Plantarum, 2020)

Genome-wide discovery of SNPs in candidate genes related to production and fertility traits in Sahiwal cattle - M. R. Vineeth; T. Surya; Jayakumar Sivalingam; Anshuman Kumar; S. K. Niranjan; S. P. Dixit; Karanveer Singh; M. S. Tantia; I. D. Gupta (Tropical Animal Health and Production, 2020)

Spatiotemporal variation of water quality index in Kanwar wetland, Begusarai, India - Ajeet Kumar Singh; M. Sathya; Satyam Verma; S. Jayakumar (Sustainable Water Resources Management, 2020)

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Tree biomass and carbon stock: understanding the role of species richness, elevation, and disturbance - Swapna S. Khadanga; Shanmuganathan Jayakumar (Tropical Ecology, 2020)

Isotherm and kinetic modeling of sorption of Cadmium onto a novel red algal sorbent, Hypnea musciformis - V. Jayakumar; S. Govindaradjane; M. Rajasimman (Modeling Earth Systems and Environment, 2019)

Health risk assessment of heavy metals in crop grains grown on open soils of Kanwar wetland, India - Ajeet Kumar Singh; M. Sathya; Satyam Verma; S. Jayakumar (Euro-Mediterranean Journal for Environmental Integration, 2018)

Boreal summer sub-seasonal variability of the South Asian monsoon in the Met Office GloSea5 initialized coupled model - A. Jayakumar; A. G. Turner; S. J. Johnson; E. N. Rajagopal; Saji Mohandas; A. K. Mitra (Climate Dynamics, 2017)

Determining shallow aquifer vulnerability by the DRASTIC model and hydrochemistry in granitic terrain, southern India - N C Mondal; S Adike; V S Singh; S Ahmed; K V Jayakumar (Journal of Earth System Science, 2017)

Assessment of shoreline changes over the Northern Tamil Nadu Coast, South India using WebGIS techniques - K. Jayakumar; S. Malarvannan (Journal of Coastal Conservation, 2016)

Toxic Effects of Couroupita guianensis Against Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) - K Baskar; S Ignacimuthu; M Jayakumar (Neotropical Entomology, 2015)

In Vitro and In Vivo Biological Evaluation of O-Carboxymethyl Chitosan Encapsulated Metformin Nanoparticles for Pancreatic Cancer Therapy - K. S. Snima; R. Jayakumar; Vinoth-Kumar Lakshmanan (Pharmaceutical Research, 2014)

Geomorphic settings of mangrove ecosystem in South Andaman Island: A geospatial approach - E YUVARAJ; K DHARANIRAJAN; S JAYAKUMAR; SARAVANAN (Journal of Earth System Science, 2014)

Distinctive effects of nano-sized permethrin in the environment - R. S. Suresh Kumar; P. J. Shiny; C. H. Anjali; Jayakumar Jerobin; Katrin Margulis Goshen; Shlomo Magdassi; Amitava Mukherjee; N. Chandrasekaran (Environmental Science and Pollution Research, 2013)

Dimethoxycurcumin-induced cell death in human breast carcinoma MCF7 cells: evidence for pro-oxidant activity, mitochondrial dysfunction, and apoptosis - A. Kunwar; S. Jayakumar; A. K. Srivastava; K. I. Priyadarsini (Archives of Toxicology, 2012)

Metal Contamination in Select Species of Birds in Nilgiris District, Tamil Nadu, India - R. Jayakumar; S. Muralidharan (Bulletin of Environmental Contamination and Toxicology, 2011)

Forest Dynamics in the Eastern Ghats of Tamil Nadu, India - S. Jayakumar; A. Ramachandran; G. Bhaskaran; J. Heo (Environmental Management, 2009)

Persistent Organochlorine Pesticide Residues in Tissues and Eggs of White-Backed Vulture, Gyps bengalensis from Different Locations in India - S. Muralidharan; V. Dhananjayan; Robert Risebrough; V. Prakash; R. Jayakumar; Peter H. Bloom (Bulletin of Environmental Contamination and Toxicology, 2008)

Genetic variations and interrelationships in Vanilla planifolia and few related species as expressed by RAPD polymorphism - D. Minoo; V. N. Jayakumar; S. S. Veena; J. Vimala; A. Basha; K. V. Saji; K. Nirmal Babu; K. V. Peter (Genetic Resources and Crop Evolution, 2008)

Inhibitory effects of short-term administration of dl-α-lipoic acid on oxidative vulnerability induced by Aβ amyloid fibrils (25–35) in mice - E. Philip Jesudason; J. Gunasingh Masilamoni; Ben S. Ashok; B’joe Baben; V. Arul; K. Samuel Jesudoss; W. Charles E. Jebaraj; S. Dhandayuthapani; S. Vignesh; R. Jayakumar (Molecular and Cellular Biochemistry, 2008)

New concepts in the mechanism of ammonia-induced astrocyte swelling - M. D. Norenberg; A. R. Jayakumar; K. V. Rama Rao; K. S. Panickar (Metabolic Brain Disease, 2007)

Influence of the macrotidal environment on the source to sink pathways of suspended flux in the Gulf of Kachchh, India: evidence from the Ocean Colour Monitor (IRS‐P4) - O. S. Chauhan; A. A. A. Menezes; S. Jayakumar; M. A. Malik; Y. Pradhan; A. S. Rajawat; S. R. Nayak; G. Bandekar; C. Almeida; M. Talaulikar; M. V. Ramanamurty; B. R. Subramanian (International Journal of Remote Sensing, 2007)

Anti-inflammatory effect of melatonin on Aβ vaccination in mice - E. Philip Jesudason; B’Joe Baben; Ben S. Ashok; J. Gunasingh Masilamoni; R. Kirubagaran; W. Charles E. Jebaraj; R. Jayakumar (Molecular and Cellular Biochemistry, 2007)

Rapid assessment on the impact of tsunami on mangrove vegetation of The Great Nicobar Island - R. Sridhar; T. Thangaradjou; L. Kannan; A. Ramachandran; S. Jayakumar (Journal of the Indian Society of Remote Sensing, 2006)

Altered structure and expression of RB1 gene and increased phosphorylation of pRb in human vestibular schwannomas - R. Thomas; P. D. Antony Herold Prabhu; J. Mathivanan; Rohini; D. Sivakumar; P. N. Jayakumar; B. Indira Devi; S. Satish; K. V. R. Sastry; R. Gope (Molecular and Cellular Biochemistry, 2005)

Heavy Metals in Feathers of Six Species of Birds in the District Nilgiris, India - S. Muralidharan; R. Jayakumar; G. Vishnu (Bulletin of Environmental Contamination and Toxicology, 2004)

Land use/land cover mapping and change detection in part of eastern ghats of tamil nadu using remote sensing and GIS - S. Jayakumar; D. I. Arockiasamy (Journal of the Indian Society of Remote Sensing, 2003)

Estimates of current status of forest types in Kolli Hill using remote sensing - S Jayakumar; D I Arockiasamy; S John Britto (Journal of the Indian Society of Remote Sensing, 2000)

Isotopic composition of nitrate in the central Arabian Sea and eastern tropical North Pacific: A tracer for mixing and nitrogen cycles - Jay A. Brandes; Allan H. Devol; T. Yoshinari; D. A. Jayakumar; S. W. A. Naqvi (Limnology and Oceanography, 1998)
The δ 15 N composition of nitrate and N 2 gas was measured in the eastern tropical North Pacific (ETNP) and central Arabian Sea (AS) suboxic regions. The δ 15 N of nitrate increased from 6‰ at 2,500 m to 15‰ at 250–350 m in both regions, while the δ 15 N of N 2 concurrently decreased from 0.6‰ to 0.25‰. The denitrification isotopic fractionation factor (ε denit ) for each region was estimated using both advection‐reaction and diffusion‐reaction models. Values for ε denit in the ETNP ranged from 25 ± 2 (advection‐reaction) to 30 ± 3 (diffusion‐reaction). Values for ε denit in the central AS varied from 22 ± 3 (advection‐diffusion) to 25 ± 4 (reaction‐diffusion) using a starting nitrate isotopic composition of 6‰ but were indistinguishable from calculated values from the ETNP when an initial value of 5‰ was employed. Based upon the model results, an average global ε denit of 27 ± 3 is proposed for marine suboxic water columns. Isotopic enrichment of nitrate in oxic waters beneath the active denitrification regions was observed and indicates the presence of significant cross‐isopycnal ventilation at depth. The isotopic composition of nitrate decreased above 250 m to −80 m, and this pattern is hypothesized to be caused by the input of isotopically light nitrogen from nitrogen fixation in the euphotic zone. A simple isotopic mass balance indicates that a significant percentage of primary productivity in the central AS may be fueled by nitrogen fixation.